Evaluation of an adjustable support shoulder exoskeleton on static and dynamic overhead tasks. (September 2018) - Van Engelhoven, Logan; Poon, Nathan; Kazerooni, Homayoon; Barr, Alan; Rempel, David; Harris-Adamson, Carisa
Introduction: Overhead tasks increase the risk of work related musculoskeletal disorders to industrial workers. A shoulder supporting exoskeleton with adjustable and angle dependent torque (referred to as shoulderX in this paper for brevity) was designed and built at the University of California Berkeley Human Engineering and Robotics Laboratory for workers performing overhead tasks. shoulderX was designed specifically to reduce the exposure to large muscle exertion forces on the shoulder complex from overhead work.Methods: We evaluated shoulderX by measuring the muscle activation of the upper trapezius (UT), anterior deltoid (AD), triceps long head (TR), and infraspinatus (IF) during static and dynamic overhead tasks. Thirteen male subjects with experience in the construction or manufacturing industries were recruited to perform overhead tasks using light (.45 kg) and heavy (2.25 kg) weight tools with four exoskeleton support levels (0, 8.5, 13.0, 20.0 Nm peak torque).Results: During all conditions, the wearer's shoulder flexor muscle activity of UT, AD were reduced with increasing strength of shoulderX by up to 80%. Subjects unanimously preferred the use of shoulderX over the unassisted condition for all task types (static and dynamic overhead tasks) and tool weights (.45 kg and 2.25 kg).Conclusion: shoulderX reduces the wearer's primary muscle activity in overhead static and dynamic work and results in a more desirable and balanced pattern of shoulder complex activation. This investigation indicates that shoulderX reduces the risk of work related shoulder injuries during overhead tasks.